Dependency of Coxiella burnetii Type 4B Secretion on the Chaperone IcmS - Larson, Charles L. (J Bacteriol, 2019)
Macrophage parasitism by Coxiella burnetii, the cause of human Q fever, requires the translocation of proteins with effector functions directly into the host cell cytosol via a Dot/Icm type 4B secretion system (T4BSS). Secretion by the analogous Legionella pneumophila T4BSS involves signal sequences within the C-terminal and internal domains of effector proteins. The cytoplasmic chaperone pair IcmSW promotes secretion and binds internal sites distinct from signal sequences. In the present study, we investigated requirements of C. burnetii IcmS for host cell parasitism and effector translocation. A C. burnetii icmS deletion mutant (ΔicmS) exhibited impaired replication in Vero epithelial cells, deficient formation of the Coxiella-containing vacuole, and aberrant T4BSS secretion. Three secretion phenotypes were identified from a screen of 50 Dot/Icm substrates: IcmS dependent (secreted by only wild-type bacteria), IcmS independent (secreted by both wild-type and ΔicmS bacteria), or IcmS inhibited (secreted by only ΔicmS bacteria). Secretion was assessed for N-terminal or C-terminal truncated forms of CBU0794 and CBU1525. IcmS-inhibited secretion of CBU1525 required a C-terminal secretion signal whereas IcmS-dependent secretion of CBU0794 was directed by C-terminal and internal signals. Interchange of the C-terminal 50 amino acids of CBU0794 and CBU1525 revealed that sites within the C terminus regulate IcmS dependency. Glutathione S-transferase-tagged IcmSW bound internal sequences of IcmS-dependent and -inhibited substrates. Thus, the growth defect of the C. burnetii ΔicmS strain is associated with a loss of T4BSS chaperone activity that both positively and negatively regulates effector translocation. IMPORTANCE The intracellular pathogen Coxiella burnetii employs a type 4B secretion system (T4BSS) that promotes growth by translocating effectors of eukaryotic pathways into host cells. T4BSS regulation modeled in Legionella pneumophila indicates IcmS facilitates effector translocation. Here, we characterized type 4B secretion by a Coxiella ΔicmS mutant that exhibits intracellular growth defects. T4BSS substrates demonstrated increased, equivalent, or decreased secretion by the ΔicmS mutant relative to wild-type Coxiella. Similar to the Legionella T4BSS, IcmS dependency in Coxiella was determined by C-terminal and/or internal secretion signals. However, IcmS inhibited secretion of some effectors by Coxiella that were previously shown to be translocated by Legionella. Thus, Coxiella has a unique IcmS regulatory mechanism that both positively and negatively regulates T4BSS export.